2005
DOI: 10.7202/706199ar
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Pinus banksiana to the European race of Gremmeniella abietina

Abstract: Au début des années 80, plus de 90 % de mortalité causée par Gremmeniella abietina, race européenne, a été relevée dans des plantations de pin rouge (Pinus resinosa) localisées à environ 200 km au nord-ouest de Montréal, Québec, Canada. Les pins gris ( Pinus banksiana) avoisinants ne semblaient pas attaqués. Les forestiers ont donc reboisé ces aires avec des semis de pin gris. Des parcelles d'études de 100 pins gris ont été établies dans trois plantations sur les quatre sélectionnées en 1988. Comme références,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…1997) but little is known about the resistance mechanisms to this disease. Recently, it has been demonstrated that jack pine is resistant to the EU race ( Laflamme and Blais 2000) and defence reactions have been described ( Simard et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1997) but little is known about the resistance mechanisms to this disease. Recently, it has been demonstrated that jack pine is resistant to the EU race ( Laflamme and Blais 2000) and defence reactions have been described ( Simard et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…abietina EU race, 2-year-old jack and lodgepole pine seedlings were planted adjacent to 25-year-old red pine trees naturally infected by the EU race (Laflamme and Blais 2000;Laflamme et al 2006). abietina EU race, 2-year-old jack and lodgepole pine seedlings were planted adjacent to 25-year-old red pine trees naturally infected by the EU race (Laflamme and Blais 2000;Laflamme et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…To test their resistance to Gremmeniella abietina var. abietina EU race, 2-year-old jack and lodgepole pine seedlings were planted adjacent to 25-year-old red pine trees naturally infected by the EU race (Laflamme and Blais 2000;Laflamme et al 2006). These plantations are located about 200 km northwest of Montreal, QC, Canada (46°39′N, 75°16′W).…”
Section: Methodsmentioning
confidence: 99%
“…In Canada, P. banksiana has shown resistance to G. abietina (EU race) under field conditions (Laflamme and Blais 2000). A histological study was conducted on these infected pine shoots; observation demonstrated that lignosuberized tissues confine the pathogen within the necrotic area (Simard et al 2001).…”
Section: Introductionmentioning
confidence: 99%